The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1111/j.1365-2044.2005.04505.x
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐operative detection of valvular heart disease by anaesthetists

Abstract: SummaryWe prospectively estimated the prevalence of heart murmurs in 2522 consecutive adult noncardiac surgery patients during pre-operative evaluation. Factors that contribute to the detection of a heart murmur were identified, and echocardiography was used to evaluate to what extent a murmur reflected presence of valvular heart disease. A cardiac murmur was detected in 106 patients (prevalence 4.2%, 95% CI: 3.5-5.1%). Multivariable logistic regression analyses showed that age and general physical impression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 26 publications
0
17
0
2
Order By: Relevance
“…A TTE at rest primarily evaluates functional and anatomical abnormalities, is a poor discriminator for active coronary artery disease and is not a substitute for pre-operative stress testing. In addition, a normal TTE study does not rule out all possible cardiac pathology (2) No TOE (2) AS, aortic stenosis; CVP, central venous pressure; HDU, high dependency unit; LV, left ventricular; PHT, pulmonary hypertension; TOE, intra-operative transoesophageal echocardiography. The number in parenthesis refers to the number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…A TTE at rest primarily evaluates functional and anatomical abnormalities, is a poor discriminator for active coronary artery disease and is not a substitute for pre-operative stress testing. In addition, a normal TTE study does not rule out all possible cardiac pathology (2) No TOE (2) AS, aortic stenosis; CVP, central venous pressure; HDU, high dependency unit; LV, left ventricular; PHT, pulmonary hypertension; TOE, intra-operative transoesophageal echocardiography. The number in parenthesis refers to the number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Successful use of focused TTE by emergency [21], intensive care [22] and trainee physicians [23] has also been demonstrated. The ability to discriminate haemodynamically significant from nonsignificant aortic stenosis is important as it is a significant risk factor for postoperative mortality [6], is relatively common [5], is often poorly assessed clinically [8,9] and may be asymptomatic even if severe [24]. This has been achieved by focused TTE without the use of quantitative Doppler (standard with comprehensive TTE) in this study, and by others [25][26][27][28] by using 2D assessment of cusp separation.…”
Section: Discussionmentioning
confidence: 99%
“…Accurate pre-operative cardiac assessment is important to devise the most appropriate anaesthetic plan [2]. Aortic stenosis, common in the hip fracture population [5], and pulmonary hypertension are significant risk factors for mortality [6,7], but diagnosis is unreliable without echocardiography [8,9]. In addition, other abnormal haemodynamic states such as hypovolaemia, left ventricular systolic and ⁄ or diastolic failure, right heart failure and vasodilatation (for example, in sepsis) often accompany acute surgical disease, and may contribute to impaired cardiac output and tissue…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with their control populations, they noted mitral valve prolapse to occur at four times the rate in patients with AIS [5,12]. However, prior data has shown no higher perioperative risk with the finding of mitral valve prolapse in asymptomatic patients [25]. Li et al [22] showed a significant decrease in RV ejection fraction in patients with severe scoliosis (major curve angles >80º) using the tricuspid annular plane systolic excursion as a surrogate for ejection fraction.…”
Section: Discussionmentioning
confidence: 99%